Some ethical consequences of economic competition - Michelman, James H. (Journal of business ethics, 1983)
Commonly accepted dictates of morality clash with the a priori laws of free economic competition. These divergent directives — that stem from the essence of their sources and cannot be changed or negated without altering their sources — contradict each other and so set up conflicts of the most fundamental kind in men's psyches (or souls). In addition, this clash of moralities implies a most serious question respecting real freedom under a system of so-called free-enterprise. For, if in order to thrive, we must perform actions that at the same time violate our own moral self respect, we cannot call ourselves free.